REDUNDANT PUBLICATION – A dilemma of Publication Ethics - Dr Fatema Jawad (Journal of the Pakistan Medical Association, 2022)
The term duplicate or redundant publication was defined by the ICMJE as: “publication of a paper that overlaps substantially with one already published, without clear, visible reference to the previous publication”.1 Redundant publication cannot be ignored by an editor. More in practice in recent times, due to the availability of the electronic gadgets, it is mainly due to the race for publishing a large number of articles for academic purposes. Lack of time, insufficient research integrity and the competition to achieve more in a short span, makes an author resort to this unethical act. Duplicate submission/publication is “the practice of submitting the same study to two journals or publishing similar contents from the same study in two journals. These submissions/publications can be nearly simultaneous or years later”.2 Both the practices are very much in use by authors because the disadvantages are either not anticipated or not known. There is also a need of a certain number of publications for their promotion or restrained due to shortage of time for conducting the research and then writing it. Authors indulging in these unethical acts do not anticipate the risks they are undertaking. Detection of such falsified acts, which is very easy, will spoil their reputation, as the matter will be reported to the head of the institution. If the article is published and later retracted due to being a redundant/duplicate publication, the fact will not remain hidden. It could become evident during an interview. In some institutions, unethical acts are given serious consideration and can lead to demotion or barrier to promotion. Continue..